(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the biggest problems in our environment is waste pollution. Low-density polyethylene (LDPE) plastics are non-biodegradable, and improper disposal of used plastics causes solid waste to accumulate and harm the environment. To address the issue above, the researchers came up with the idea of generating bioplastic using starch as a construction material, which could be a solution to decrease waste pollution. The results of the study are acceptable for both chemical and environmental engineers in terms of construction materials, design and procedure, environmental impact, durability, and presentation. The results are also acceptable for both chemical and environmental engineers in terms of environmental impact, durability, and presentation. It indicates that there is no significant difference between and among the assessments of the two groups of respondents in terms of construction materials, design and procedure, environmental impacts, durability, and presentation. The overall mean of the chemical engineers is 3.34 with a variance of 0.034, a t-computed of 1.282, a degree of freedom of 8, and a t-critical of 3.355. The t-computed is t-critical; therefore, the assessment of the chemical engineers is highly acceptable. The overall mean of environmental engineers is 3.19 with a variance of 0.034, a t-computed of 1.282, a degree of freedom of 8, and a t-critical of 3.355. The t-computed is t-critical; therefore, the assessment of environmental engineers is acceptable. There is no significant difference between the assessments of the two groups of respondents in terms of the aforementioned variables. For further enhancement and improvement of the project, the ensuing discussions and the recommendations proposed are as follows: perform a method for bioplastic testing to know the properties of the bioplastic. For a better outcome, try to generate the product inside the testing center.